MENGIDENTIFIKASI PENGAJARAN YESUS MENURUT INJIL MATIUS 5-7 DAN APLIKASINYA BAGI GURU PENDIDIKAN AGAMA KRISTEN - Nainggolan, Yeheszkiel Daud Sahala (Sekolah Tinggi Teologi Kadesi Bogor, 2023)
Every teaching is selected and utilized to suit the circumstances and requirements of its audience. Each meeting differs as educators comprehend the intrinsic nature of each individual, both in general and as unique individuals. The interaction between teacher and student manifests changes in the student's character and fosters rapid intellectual growth. Such pedagogy can guide students in comprehending their faith through the teachings of Jesus Christ. Jesus, as a teacher, imparted truths capable of nurturing human character. The fundamental principle of Jesus's teachings consistently pertained to educational matters, aiming to shape an individual's character and infuse a spiritual essence, harmonizing it with their being. In his teachings, Jesus consistently imbued Christian culture and employed language congruent with personal experiences, societal concerns, customary practices, family life, and religious concepts.